2019
DOI: 10.4236/wjcd.2019.95029
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study on Assessment of Oxidative Stress in Coronary Heart Disease Patients in Bangladesh

Abstract: Oxidative stress is considered a central factor in endothelial dysfunction and plaque formation in coronary heart disease (CHD) patients. In this crosssectional study, the stress-induced protein and lipid oxidation and production of signaling molecule, nitric oxide has been investigated in CHD patients in Bangladesh. A total of 140 participants were enrolled of which 70 were CHD patients, and the remaining 70 were control subjects having no cardiovascular disease. The diagnosis of CHD was made by expert physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 25 publications
4
3
0
Order By: Relevance
“…All major risk factors for atherosclerosis such as hyperlipidemia, diabetes, hypertension, and smoking have been found associated with reduced NO bioavailability [33]. In the current study, the nitric oxide level was significantly lower in the ACS patients, which was consistent with previous findings [20] [34].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All major risk factors for atherosclerosis such as hyperlipidemia, diabetes, hypertension, and smoking have been found associated with reduced NO bioavailability [33]. In the current study, the nitric oxide level was significantly lower in the ACS patients, which was consistent with previous findings [20] [34].…”
Section: Discussionsupporting
confidence: 92%
“…It may be mentioned that due to stringent inclusion criteria, it was difficult to obtain samples from age-matched control subjects. Further, smoking and previously diagnosed hypertension appeared to be significant risk factors for the development of ACS, as reported earlier [20] [25]. Previous investigators observed that the vascular NADPH oxidase (NOX) was linked to the pathological states associated with hypertension and endothelial [26].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The most widely used biomarker for oxidative damage to proteins is protein carbonyls that reflects cellular damage induced by multiple forms of ROS [ 9 ]. In the present study, the protein carbonyls of the ACS cases were significantly higher than the controls, which agreed with previous findings [ 22 , 32 ]. In addition, a protein carbonyl level greater than 2.21 nmol/mg with a sensitivity and specificity of 83.0 and 79.7% showed its association with ACS.…”
Section: Discussionsupporting
confidence: 94%
“…The IMA in the serum was determined according to the method of Bar-Or et al [ 7 ] and detailed previously [ 20 ]. Protein oxidation was estimated by measuring the protein carbonyl content of the plasma samples by the method described by Levine et al [ 21 ] and detailed previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%